A unified creep interaction factor to characterize multiple cracks interaction at elevated temperatures. (January 2020) - Xu, Lianyong; Zhao, Lei; Gao, Zhifang; Han, Yongdian; Jing, Hongyang
Highlights: Unified interaction factor normalized by creep strain between two and single cracks. Position dependence diminished and maximum intensity trend retained. Unified interaction factor controlled by crack depth, distance and hardening exponent. A criterion of interaction factor at 1.25 was adopted for combining interacting cracks. Abstract: Multiple cracks are inevitable to simultaneously occur in components, the growth and coalescence of which greatly reduced loading capacity of defected components at elevated temperatures. Considering the driving force of crack growth determined by the equivalent creep strain ahead of crack front, this paper proposed a unified creep interaction factor based on the ratio of the equivalent creep strain area between multiple cracks and single crack at the same creep strain isoline. This proposed interaction factor successfully demonstrated the interaction among coplanar cracks, eliminated the dependence of position along the crack front and retain the development trend of the maximum creep interaction. The proposed unified factor was greatly influenced by crack depth and creep hardening exponent, besides crack distance. Moreover, through the analyses of the variation of the crack growth rate in the cases of multiple cracks or single crack, the combination rule of multiple cracks could be determined by the value of the interaction level and thus the criteria for combination of interacting multiple cracks was proposed.